USP21 prevents the generation of T-helper-1-like Treg cells - Yangyang Li (Nature Portfolio, 2016)
The immunosuppressive role of regulatory T (Treg) cells largely depends on their virtue of expressing the transcription factor FOXP3. Here the authors show that the E3 deubiquitinase USP21 stabilizes FOXP3 by mediating its deubiquitination and helps to maintain the expression of Treg signature genes and Treg lineage stability in mice.